2003
DOI: 10.1002/jmor.10097
|View full text |Cite
|
Sign up to set email alerts
|

Compartmental fasciotomy and isolating a muscle from neighboring muscles interfere with myofascial force transmission within the rat anterior crural compartment

Abstract: Muscles within the anterior crural compartment (extensor digitorum longus, EDL; tibialis anterior, TA; and extensor hallucis longus, EHL) and within the peroneal compartment were excited simultaneously and maximally. All muscles were kept at constant length with the exception of EDL, for which muscle length was changed by moving its proximal tendon. Active and passive force was measured at proximal as well as distal EDL tendons and at the combined distal tendons of TA and EHL (TA+EHL). In the initial experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…Previous studies using rats have clearly shown that connective tissue linkages between synergistic muscles are capable of transmitting substantial forces Huijing et al, 2003;Maas et al, 2001Maas et al, , 2004Maas et al, , 2005. However, these studies involved several aspects that were non-physiological.…”
Section: Effects Of Knee Angle On 3d Ankle Moments Of So Musclementioning
confidence: 99%
“…Previous studies using rats have clearly shown that connective tissue linkages between synergistic muscles are capable of transmitting substantial forces Huijing et al, 2003;Maas et al, 2001Maas et al, , 2004Maas et al, , 2005. However, these studies involved several aspects that were non-physiological.…”
Section: Effects Of Knee Angle On 3d Ankle Moments Of So Musclementioning
confidence: 99%
“…In vivo, the relationships change slightly because of submaximal muscle activations, 14,27 the interactions between muscles and connective tissues, 15 and tendon elasticity. 18 However, they should be considered as an accurate general framework for muscle physiology.…”
Section: Muscle Physiologymentioning
confidence: 99%
“…Because fascia attaches to and envelops many limb muscles, it is often hypothesized that it broadens the insertion of muscles, distributing or redirecting muscle force transmission [1][2][3][4] . Several studies have shown that disrupting the fascia 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 3 between or around muscles decreases the muscle's force output [1][2][3] . Fascial continuity among limb segments and between the limbs and the trunk have led others to posit that fascia plays a role in transferring load and coordinating movement among limb segments and body regions [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%